Systematic revision of the genus Rana in South India (Zoological Records and Reviews, 2021)
The genus Rana (Linnaeus, 1758) in South India has historically been subject to extensive taxonomic confusion, withnumerous species described, synonymised, and re-elevated across nearly two centuries of systematic work. Despiterecent molecular revisions of the broader Ranidae family, South Indian Rana diversity remains incompletelycharacterised, with several morphologically diagnosable populations lacking formal species status. This study presents asystematic revision of the genus Rana in South India based on integrative analysis of morphometric data (22 variables),qualitative external characters, and mitochondrial sequence data (16S rRNA and cytochrome b) from 318 individualsspanning 24 sampling localities across the Eastern Ghats, Western Ghats, and Deccan Plateau. Bayesian and maximumlikelihood phylogenetic analyses consistently recover five well-supported South Indian Rana lineages, two of which areherein recognised as valid species following integrative assessment: Rana ghatsensis sp. nov. from the moist deciduousforests of the Eastern Ghats, and Rana deccanensis sp. nov. from plateau grassland habitats. Updated synonymies, arevised dichotomous identification key, and complete morphometric diagnoses are provided for all recognised SouthIndian Rana taxa. Four additional populations representing potential undescribed diversity are flagged for priorityinvestigation. Habitat assessments indicate that three of the five lineages face significant range contraction due toagricultural expansion and forest fragmentation.